2007
DOI: 10.1080/08039480701773253
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial functioning needs attention in adolescent eating disorders

Abstract: We studied the differences in psychosocial functioning in the early stages of adolescent anorexia nervosa (AN) and bulimia nervosa (BN). The study group comprised 57 adolescent eating disorder (ED) outpatients (girls). Psychosocial functioning was evaluated by GAF (Global Assessment of Functioning), and by Morgan-Russell psychosocial subscales. GAF scores were very low in both AN and BN. On the Morgan-Russell subscales, bulimics reported more unsatisfactory relationships with family and impairment in work/scho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 28 publications
1
13
0
Order By: Relevance
“…This finding is consistent with previous questionnaire studies (Claes et al, 2005;Diaz-Marsa et al, 2000;Penas-Lledo et al, 2002) and with observations of impulsive traits and behaviours in BN individuals (Bridgeman & Slade, 1996;Holderness et al, 1994;Ruuska et al, 2005).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…This finding is consistent with previous questionnaire studies (Claes et al, 2005;Diaz-Marsa et al, 2000;Penas-Lledo et al, 2002) and with observations of impulsive traits and behaviours in BN individuals (Bridgeman & Slade, 1996;Holderness et al, 1994;Ruuska et al, 2005).…”
Section: Discussionsupporting
confidence: 82%
“…Some common manifestations of impulsivity in BN include alcohol or substance abuse, self-harm and shoplifting, with reported incidence rates across these co-morbities ranging from 12 to 56% (Bridgeman & Slade, 1996;Holderness, Brooks-Gunn & Warren, 1994;Ruuska, Kaltiala-Heino, Rantanen & Koivisto, 2005). Patients with BN also show elevated levels of impulsive thoughts and actions on assessments via self-report questionnaires (Claes, Vandereycken & Vertommen, 2005;Diaz-Marsa, Carrasco & Saiz, 2000;Penas-Lledo, Vaz, Ramos & Waller, 2002).…”
mentioning
confidence: 99%
“…Yet cognitive decline and impaired concentration can accompany starvation and depression when the illness becomes entrenched 12. Limited research has noted deficits in combined educational or occupational roles13 and impaired concentration,14, 15 and body image disturbance has been inversely correlated to grade point average in college students 16. A large population-based twin study reported no significant differences in educational attainment between individuals with AN, their unaffected twins, and a healthy control group.…”
Section: Educationmentioning
confidence: 99%
“…Several studies suggest that women with eating disorders may have access to a similar amount of social support as control subjects, but they are nonetheless dissatisfied with their support network and feel anxious, inadequate and alienated from others (Jacobson & Robins, 1989). Difficulties in interpersonal relationships have been reported as potential factors in the development and maintenance of body image disturbance and altered eating disorders (Fairburn, Cooper, & Shafran, 2003; Ruuska, Koivisto, Rantanen, & Kaltiala‐Heino, 2007). Especially in adolescence, the development of peer relationships is particularly important.…”
Section: Introductionmentioning
confidence: 99%